2014
DOI: 10.1118/1.4900603
|View full text |Cite
|
Sign up to set email alerts
|

Registration of clinical volumes to beams‐eye‐view images for real‐time tracking

Abstract: Purpose: The authors combine the registration of 2D beam's eye view (BEV) images and 3D planning computed tomography (CT) images, with relative, markerless tumor tracking to provide automatic absolute tracking of physician defined volumes such as the gross tumor volume (GTV). Methods: During treatment of lung SBRT cases, BEV images were continuously acquired with an electronic portal imaging device (EPID) operating in cine mode. For absolute registration of physician-defined volumes, an intensity based 2D/3D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…For example, a tracking algorithm developed by Rottmann et al has been used to estimate tumor movement by automatically detected imaging features on sequential EPID frames . This tracking algorithm has found many potential applications in the clinic, including the estimation of delivered radiation dose, tumor localization, and real‐time dynamic multileaf collimator (DMLC) tracking …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a tracking algorithm developed by Rottmann et al has been used to estimate tumor movement by automatically detected imaging features on sequential EPID frames . This tracking algorithm has found many potential applications in the clinic, including the estimation of delivered radiation dose, tumor localization, and real‐time dynamic multileaf collimator (DMLC) tracking …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] For example, a tracking algorithm developed by Rottmann et al has been used to estimate tumor movement by automatically detected imaging features on sequential EPID frames. 4 This tracking algorithm has found many potential applications in the clinic, including the estimation of delivered radiation dose, 6 tumor localization, 7,8 and real-time dynamic multileaf collimator (DMLC) tracking. 9 Despite the promise of auto-tracking in adaptive radiotherapy and motion management, the performance can be greatly hindered by the EPID image quality, especially compared to kilovoltage x-ray systems.…”
Section: Introductionmentioning
confidence: 99%
“…If a tumor happens to be temporarily out of the planned position, the dosimetric differences may be exacerbated compared to treatment using longer beam on times. 6 The feasibility of markerless lung tumor tracking in 2D has been reported by a number of groups using the MV treatment beam [7][8][9][10][11][12] or kV imaging systems. [13][14][15] Using EPID movie-based tumor tracking, Richter et al 7 showed in 40 patients treated using static beams that the difference between automatic and manual tracking was a maximum of 2 mm for 98.3% in the X-direction and 89.4% in the Y -direction.…”
Section: Introductionmentioning
confidence: 99%
“…Several markerless lung tumor tracking methods have been proposed using MV electronic portal imaging devices (EPID) (Richter et al , 2010; Rottmann et al , 2013; Bryant et al , 2014; Serpa et al , 2014) or kV imaging systems (Hugo et al , 2010; Lewis et al , 2010; Gendrin et al , 2012; Yang et al , 2012; van Sornsen de Koste et al , 2015). MV EPID based methods are limited by the treatment field size and poor contrast.…”
Section: Introductionmentioning
confidence: 99%